2008
DOI: 10.1007/s10903-008-9143-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Mental Health Consultations Among Recent Chinese Immigrants in British Columbia, Canada: Implications for Mental Health Risk and Access to Services

Abstract: Linked immigration and health administrative databases were analyzed to study the factors associated with the rate of mental health consultations with physicians in 1992-2001 of over 150,000 Chinese immigrants in British Columbia, Canada. Results showed that number of years since landing and rate of non-mental health visits to general practitioners were the most consistent variables associated with mental health consultations to general practitioners and psychiatrists in all sex and age groups. Other variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
5
44
0
Order By: Relevance
“…Register studies are also restricted by the health data that is recorded. Important background information for migrants, such as reasons for migration, length of stay, or health behavior data are typically not reported in health registers [54, 61]. …”
Section: Discussionmentioning
confidence: 99%
“…Register studies are also restricted by the health data that is recorded. Important background information for migrants, such as reasons for migration, length of stay, or health behavior data are typically not reported in health registers [54, 61]. …”
Section: Discussionmentioning
confidence: 99%
“…1 The proportion of immigrants in Canada has risen for decades, and currently stands at 18% of the Canadian population. Numerous studies in Canada and elsewhere have examined different aspects of the mental health needs and treatments among immigrant groups [2][3][4][5][6] ; nonetheless, limited data are available on immigrants with BD. The estimated lifetime prevalence of BD is in the range of 1% to 2% 7,8 ; therefore, there are likely up to 100 000 immigrants with BD in Canada.…”
mentioning
confidence: 99%
“…The issue of loss of familial support due to changes in the immigrants' socio-cultural reality appeared to be an extremely important factor that created a major disruption in their familiar help-seeking pathway. Studies have indicated higher distress among Chinese individuals who are in confl ict with their families due to the cultural emphasis on harmonious family relationships (Abe-Kim et al, 2002;Chen et al, 2008). In the case of the study participants, the culture-specifi c feelings of shame associated with their personal failure and fear of judgement from family and peers (Segal, 2002;Sue & Sue, 2003) became a deterrent to seeking support and advice as well as a stressor that severely undermined their mental health both prior to and after the onset of their mental illness.…”
Section: Changes Of Socio-cultural Reality and Help-seeking Pathwaymentioning
confidence: 99%